Online Religious Coping Intervention and Post-Traumatic Social Withdrawal for Landslide Survivors - Cintami Farmawati; Nadhifatuz Zulfa; Sitti Rahmah Marsidi (Kuras Institute, 2026)
Post-traumatic social withdrawal is a common psychological impact experienced by natural disaster survivors and has the potential to hinder the recovery process. In the digital era, online religious-based support is an easily accessible alternative intervention and is considered capable of supporting the psychological adaptation process. This study aims to test the effectiveness of online religious coping intervention in reducing post-traumatic social withdrawal levels in landslide survivors in Batang Regency. The study used an experimental design with two groups: an experimental group that received the intervention and a control group without treatment. Measurements were conducted at the pretest and post-test stages. Data analysis used the Mann-Whitney U test to examine differences between groups. The results showed that the experimental group experienced a significantly greater reduction in post-traumatic social withdrawal (mean pretest = 49.00; post-test = 25.40) compared to the control group (mean pretest = 50.00; post-test = 45.20). Statistical tests showed a significant difference in post-test scores (p < 0.05), but not in pre-test scores. These findings indicate that online religious coping interventions are effective in reducing post-traumatic social withdrawal symptoms. This research contribution underscores the importance of a technology-based spiritual approach as an adaptive psychological recovery strategy, particularly in disaster contexts and in communities with religious ties. It also broadens understanding of the integration of religious values ​​into modern psychosocial interventions.